GENERASI DIGITAL CERDAS MEMBANGUN LITERASI DIGITAL DAN KEWARGANEGARAAN DIGITAL UNTUK REMAJA - Husna, Lenny; Realize , Realize; Putri , Anggia Dasa (ASOSIASI IDEBAHASA KEPRI, 2025)
The Community Service Program titled “Smart Digital Generation: Building Digital Literacy and Digital Citizenship for Adolescents” was carried out in the Maitri Indah Housing Complex and Kodim area, Buliang Subdistrict, Batu Aji District. The program aimed to deepen adolescents’ understanding of the importance of digital literacy, ethical online behavior, and legal awareness in the digital environment. Conducted over five well-structured sessions, the program used a blend of presentations, participatory discussions, and digital case simulations. The materials covered included digital literacy basics, ethical digital communication, hoax prevention, personal data protection, and understanding legal consequences in cyberspace. Participants responded enthusiastically, demonstrating active involvement and improved comprehension in using technology responsibly. The program also included hands-on training such as creating positive digital content and using basic digital safety tools. Overall, the initiative significantly contributed to shaping adolescents who are not only digitally competent but also ethically responsible and aware of their rights and obligations as digital citizens. For future sustainability, ongoing monitoring and community-based mentoring are recommended. The integration of digital tools and project-based learning made this a strategic approach to preparing youth for responsible participation in today’s digital society